Knockout of Density-Enhanced Phosphatase-1 Impairs Cerebrovascular Reserve Capacity in an Arteriogenesis Model in Mice. (20th August 2013) - Hackbusch, Daniel; Dülsner, André; Gatzke, Nora; Krüger, Janine; Hillmeister, Philipp; Nagorka, Stephanie; Blaschke, Florian; Ritter, Zully; Thöne-Reineke, Christa; Böhmer, Frank-D.; Buschmann, Ivo; Kappert, Kai
Abstract : Collateral growth, arteriogenesis, represents a proliferative mechanism involving endothelial cells, smooth muscle cells, and monocytes/macrophages. Here we investigated the role of Density-Enhanced Phosphatase-1 (DEP-1) in arteriogenesis in vivo, a protein-tyrosine-phosphatase that has controversially been discussed with regard to vascular cell biology. Wild-type C57BL/6 mice subjected to permanent left common carotid artery occlusion (CCAO) developed a significant diameter increase in distinct arteries of the circle of Willis, especially in the anterior cerebral artery. Analyzing the impact of loss of DEP-1 function, induction of collateralization was quantified after CCAO and hindlimb femoral artery ligation comparing wild-type and DEP-1 −/− mice. Both cerebral collateralization assessed by latex perfusion and peripheral vessel growth in the femoral artery determined by microsphere perfusion and micro-CT analysis were not altered in DEP-1 −/− compared to wild-type mice. Cerebrovascular reserve capacity, however, was significantly impaired in DEP-1 −/− mice. Cerebrovascular transcriptional analysis of proarteriogenic growth factors and receptors showed specifically reduced transcripts of PDGF-B. SiRNA knockdown of DEP-1 in endothelial cells in vitro also resulted in significant PDGF-B downregulation, providing further evidence for DEP-1 in PDGF-B gene regulation. In summary, our data support the notion of DEP-1 as positive functional regulator in vascular cerebral arteriogenesis, involving differential PDGF-B gene expression.